Nonlinear active disturbance rejection mechanism based sliding mode control for enhancing electric power assisted steering performance. - Tuan Anh Nguyen; Tung Lam Nguyen (PLoS ONE)
Electric Power Assisted Steering (EPAS) systems provide vehicle stability and safety under various driving conditions. Previous studies often applied only one or several traditional algorithms to control the performance of EPAS systems and ignored the influence of external disturbances. This increases the signal tracking error and causes other adverse effects on the system. In this article, we propose designing a nonlinear robust control mechanism that combines Sliding Mode Control (SMC) and Nonlinear Active Disturbance Rejection Control (NADRC) techniques to solve the existing issues. The article's novelty lies in utilizing a Nonlinear Extended State Observer (NESO) and Nonlinear Tracking Differentiator (NTD) to improve the performance of the proposed control mechanism. In addition, ideal assisted characteristic curves have been innovated based on nonlinear functions to improve the vehicle's driving comfort and stability, which is considered the second new contribution. The simulation results show that most of the steady-state errors of the proposed controller are only about 2% (v1 =  30 km/h) and no more than 3.5% (v2 =  70 km/h) except for steering motor current. The observed errors of the state variables are less than 1.4%, while the disturbance error is only about 6.9%. Finally, it is claimed that common issues like overshoot, chattering, and sensor noise do not affect the EPAS system when the proposed method is used to control it.